2000
DOI: 10.1034/j.1399-6576.2000.440808.x
|View full text |Cite
|
Sign up to set email alerts
|

Onset and offset of intrathecal morphine versus nalbuphine for postoperative pain relief after total hip replacement

Abstract: We conclude that after total hip replacement, administration of intrathecal nalbuphine resulted in a significantly faster onset of pain relief and shorter duration of analgesia than intrathecal morphine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 24 publications
5
56
0
2
Order By: Relevance
“…Nalbuphine is widely studied as an adjuvant to local anesthetics in central neuraxial techniques to improve the quality of perioperative analgesia as it provides reasonably potent analgesia for visceral nociception. 4,5 Clonidine and nalbuphine are freely available and absence of neurotoxicity has already been established. Not much studies have been conducted to compare the clonidine with nalbuphine as intrathecal adjuvants to bupivacaine.…”
Section: Introductionmentioning
confidence: 99%
“…Nalbuphine is widely studied as an adjuvant to local anesthetics in central neuraxial techniques to improve the quality of perioperative analgesia as it provides reasonably potent analgesia for visceral nociception. 4,5 Clonidine and nalbuphine are freely available and absence of neurotoxicity has already been established. Not much studies have been conducted to compare the clonidine with nalbuphine as intrathecal adjuvants to bupivacaine.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that incidence of adverse effects like pruritus and postoperative nausea and vomiting is lower with nalbuphine in comparison with morphine. [4][5][6][7][8][9] Reviews on preclinical pharmacology of this drug suggest that nalbuphine moiety is approximately 10 times more pharmacologically potent than the mixed opioid agonist-antagonist butorphanol on an "antagonist index" scale, which quantitates the drug's ability to act both as an analgesic (via opioid κ-receptor agonism) and as a µ-receptor antagonist. 10 The opioid antagonist activity of nalbuphine is one-fourth as potent as nalorphine and 10 times that of pentazocine.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pain can lead to a multitude of potentially life-threatening adverse physiological and psychological ORIGINAL ARTICLE 1 Senior Resident, 2 Associate Professor, 3,4 Assistant Professor 5 Professor and Head [1][2][3][4][5] Department of Anesthesiology,Critical Care and Pain Medicine, Byramjee Jeejeebhoy Government Medical College and Sassoon General Hospitals, Pune, Maharashtra, India disturbances. A systemic stress response is initiated due to pain and tissue injury associated with surgery, which has neuroendocrine, immunological, and hematological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Other opioids are also used with the same goal, such as fentanyl 3,4 , sufentanil 5,6 , oxymorphone 7 , and especially morphine 1,[8][9][10][11] . Epidural use of morphine has been limited though because of the dose-dependent risk of delayed respiratory depression and/or potential urinary retention requires close monitoring of respiratory patterns, which is not always possible in dogs 11,12 and humans 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The respiratory depression induced by opioids is primarily mediated by the μ-receptor agonist activity. The μ-antagonist properties of the nalbuphine should produce fewer μ-mediated side effects such as respiratory depression, pruritus, nausea and vomiting 13,14 .…”
Section: Introductionmentioning
confidence: 99%